Performance improvement of direct torque controlled interior mounted permanent magnet drives by employing a linear combination of current and voltage based flux observers. Issue 10 (1st August 2016) - Koc, Mikail; Sun, Tianfu; Wang, Jiabin
Abstract : Flux observers in direct torque controlled (DTC) motor drives are of paramount importance as the drives rely on estimated variables for feedback control. It is well‐known that current‐based (CB) estimations are advantageous at low speeds, whereas voltage‐based (VB) estimations are more accurate at high speeds. Hence, a large number of state‐of‐the‐art DTC drives utilise closed‐loop flux observers in which the CB and VB estimations become dominant at low and high speeds, respectively. However, it has been discovered that the performance and current waveforms with the closed‐loop observers significantly deteriorate at low speeds since the residual error of the VB estimation causes current distortions. In addition, these observers have non‐linear flux transition trajectory resulting in reduced accuracy during transitions. To improve the low speed performance and achieve the linear transition, an alternative combination of the two estimations is proposed. Experimental results on a 10 kW interior mounted permanent magnet machine drive designed for electric vehicle traction applications validate significant improvements on the drive performance.